Project Management of Strengthening Pancasila Learner Profile for Learner Character Development - Muhammad Khairul Irfan; R. Madhakomala (Ravine Publisher, 2024)
The background of this research is to analyze how the implementation of the project for strengthen the profile of Pancasila students can develop the character of students. This research aims to analyze the application of management concepts (planning, organizing, implementing and controlling) in the project for strengthen the profile of Pancasila students and how to implement the project for strengthen the profile of Pancasila students in order to develop the character of students. The method used in this research is included in qualitative research, with the method used being a literature study, and the data sources used are journals and books that are relevant to this research. This research provides an understanding of the management of the project for strengthen the profile of Pancasila students by optimizing all management functions for the project for strengthen the profile of Pancasila students and develop their character. Planning for the Project for Strengthening the Profile of Pancasila students must be carried out carefully so that its implementation can run effectively. Project implementation includes the initial stages, implementation and celebration of the project. Evaluation for the Strengthening Pancasila Profile Project focuses on the process and not the final result. Schools can also create evaluation instruments (assessments) that are appropriate to the school's circumstances.